The Story Behind the IFAS Assessment of Non-native Plants in Florida's Natural Areas - Alison M. Fox; Doria R. Gordon; Joan A. Dusky; Linda Tyson; Randall K. Stocker; Kenneth A. Langeland; Aimee L. Cooper (EDIS)
Revised! SS-AGR-86, an 8-page fact sheet by A. M. Fox, D. R. Gordon, J. A. Dusky, L. Tyson, R. K. Stocker, K. A. Langeland, and A. L. Cooper, provides a history, justification, and summary of the IFAS Assessment of Non-Native Plants in Florida’s Natural Areas. Includes references. Published by the UF Department of Agronomy, November 2009.